Effect of net presence, interaction type, and ball type on student participation and perception of tasks for the overhead initiation in volleyball - J. M. Palao; S. Guzmán (Asociación Española de Ciencias del Deporte, 2010)
The purpose of this paper was to find out the effect of net presence, interaction type, and ball type on student quantitative and qualitative participation and perception in volleyball games of 1-on-1 (both cooperative and competitive). The sample consisted of 31 undergraduate Physical Activity and Sport students. A quasi-experimental, transversal and inter-group design was used. The independent variables were: net presence, interaction type (cooperative and competitive), and ball type (beach, foam, and official). The dependent variables were: number of contacts, number of interruptions, execution quality (height of contact, use of kinetic chain, and contact in front of the body), level of participation, ratio of repetitions-to-time, and student perception of the effect of the variables modified in relation to enjoyment, play continuity, and execution. The results show that in the overhand touch initiation: a) the competitive situations of 1-on-1 with net presented a higher number of contacts and level of participation; and b) the students analyzed perceived correctly the effect of the player interactions (cooperative and competitive), but they did not perceive correctly the effect of net presence and ball type. Key words:initiation, task modifications, volleyball, overhead.